A study of awareness of the implementation of green event among UiTM students at UiTM Pahang / Nur Afiqah Jamrin, Nurul Zafirah Samah and Siti Nur Atirah Azmi - Jamrin, Nur Afiqah; Samah, Nurul Zafirah; Azmi, Siti Nur Atirah (2013)
The study was conducted to find out the Awareness of The Implementation of Green Event among Uitm Students at Uitm Pahang. The economic, social and environment is the independent variable and dependent variable was green event. Researcher received an information by distributed the questionnaire to among the students from the Bachelor Degree student of UiTM Pahang from semester 4 until semester 6. The 56 questionnaires each were randomly distributed to them and the real and corrected data that received by the researcher was 40 questionnaires. The findings stated that green event given a lot of changes in term of economic, social and environment. Researcher also found out that most of the organizer aware about the environment. Most of Bachelor Student's in UiTM Pahang, strongly have the awareness about the green event management while conduct the events . This mean that they learned to be aware about the environmentally by actively applied how to be green by conducted the event specifically. Some recommendations, needed to be applied and suggested to UiTM Jengka to make the green event successfully managed and organized.